Role of Different Subpopulations of CD8+ T Cells during HIV Exposure and Infection - Gonzalez, Sandra Milena; Taborda, Natalia Andrea; Rugeles, María Teresa (Frontiers in Immunology, 2017)
During HIV infection, specific responses exhibited by CD8+ T cells are crucial to establish an early, effective and sustained viral control, preventing severe immune alterations and organ dysfunction. Several CD8+ T cells subsets have been identified, exhibiting differences in terms of activation, functional profile and ability to limit HIV replication. Some of the most important CD8+ T cells subsets associated with viral control, production of potent antiviral molecules and strong polyfunctional responses, include Tc1 and Tc17 cells. In addition, the expression of specific activation markers has been also associated with a more effective response of CD8+ T cells, as evidenced in HLA-DR+CD38- cells. CD8+ T cells in both, peripheral blood and gut mucosa, are particularly important in individuals with a resistant phenotype, including HIV-exposed seronegatives (HESNs), long term non-progressors (LTNPs) and HIV-controllers. Although the role of CD8+ T cells has been extensively explored in the context of an established HIV-1 infection, the presence of HIV-specific cells with effector abilities and a defined functional profile in HESNs, remain poorly understood. Here, we reviewed studies carried out on different subpopulations of CD8+ T cells in relation with natural resistance to HIV infection and progression.